CONGRUENT AND INCONGRUENT COLLOCATIONS TOWARDS A BILLINGUAL PREPOSITION AND NOUN COLLOCATIONS DICTIONARY OF ENGLISH AND INDONESIAN - Sari, Dewi Wulan (UG Journal, 2021)
Collocation is a combination of words in a language that happens very often and more frequently than it would happen by chance. The writer chooses this topic because collocation is a serious problem for most Indonesian students. The problems of this research are (1) What are the equivalents of English preposition + noun collocation in Indonesian?, (2) Which preposition + noun collocations are congruent identified in the Oxford Collocation Dictionary for Students of English?, (3) Which preposition + noun collocations are incongruent identified in the Oxford Collocation Dictionary for Students of English?. The aims in this research are (1) To find out the equivalents of the sentences containing English preposition + noun collocations in Indonesian. (2) To find out the congruent preposition + noun collocations from the data found in the Oxford Collocation Dictionary for Student of English. (3) To find out the incongruent preposition + noun collocations from the data found in the Oxford Collocation Dictionary for Student of English. The source of the data was Oxford Collocations Dictionary for Students of English. The number of collocations taken as the sample of the data was 2050 English preposition + noun collocations. Qualitative and Quantitative methods are used in this research. The results of this research are (1) the result of the translation shows congruent, incongruent, and non-collocation, (2) 401(19,56%) congruent collocations “preposition + noun” are found, (3) 1584 (77,27%)incongruent collocations “preposition + noun” are found, (4) 65 (3,17%) non-collocations are found.